The Use of Guidedâ€“Questions Combined with Buzz Group Technique to Increase Studentsâ€™ Writing Skill of SMP Muhammadiyah Pagaralam - M. Bambang Purwanto; Ariya Agustin (Esteem Journal of English Education Study Programme, 2021)
Buzz Group Tehcnique Â are a technique in teaching which divide students into a group activity in which groups of students have a brief discussion (for example, five minutes) to generate ideas or answer specific questions. Â Buzz group can be used in many different ways and are most often used in combination with other techniquesâ€. In this research the writer will combined two kinds of technique, Guided-question Combined with Buzz Group Technique. Guided-question Combined with Buzz Group Technique means combine two kinds of technique in teaching learning process those are Guided-question with Buzz Group Technique to enhance both techniques. The research design used in this study was one-group pre test-post test design. The study employed both quantitative and qualitative data analyses fromÂ  pre-and post-tests, a questionnaire, and an interview. The participants of theÂ  study wereÂ  35Â  first-yearÂ  studentsÂ  enrollingÂ  inÂ  aÂ  compulsory readingÂ  courseÂ  called Communication and Reading Skills at Darussalam Polytechnic of Palembang.Â  It is shown shown by a significant difference in quality of studentsâ€™ in-class written experimental designs between the treatment and control groups (19.943 versus 17.943; p>0.0489). However, draft (22.337 versus 18.929; p>0.0760) and paper grades (27.186 versus 27.971; p>0.6726) did not vary significantly whether or not students were provided with the guided questions. There were several intervening and potentially confounding factors, due to the nature of the paper writing process in our labs, which included peer review of paper drafts that were not limited to students within the treatment and control groups.. The results suggested that 1) The English writing ability post test mean score of students was higher than the pre test mean score at the 0.05 level of significance; 2) most students were satisfied with their own writing ability; 3) they enjoyed working inÂ  group andÂ  agreed thatÂ  mindÂ  mapping technique wasÂ  aÂ  useful technique and can be applied to non- English subjects. Findings and implications for further research are discussion.Â